2015
DOI: 10.1063/1.4934508
|View full text |Cite
|
Sign up to set email alerts
|

Electron affinity of cubic boron nitride terminated with vanadium oxide

Abstract: Submitted for the 4CF15 Meeting of The American Physical SocietyElectron affinity of cubic boron nitride terminated with vanadium-oxide YU YANG, TIANYIN SUN, JOSEPH SHAMMAS, MAN-PUNEET KAUR, MEI HAO, ROBERT NEMANICH, Arizona State University -H-terminated cubic boron nitride (c-BN) has been shown to exhibit a negative electron affinity (NEA) surface, which may enable applications in thermionic and photon-enhanced energy conversion devices. The ability to withstand high temperature operation is an important fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…This is supported by the experimental results of the H-terminated c-BN with negative electron affinity. 13,14,40…”
Section: Electronic Properties Of Pristine and H-terminated C-bn(100)...mentioning
confidence: 99%
“…This is supported by the experimental results of the H-terminated c-BN with negative electron affinity. 13,14,40…”
Section: Electronic Properties Of Pristine and H-terminated C-bn(100)...mentioning
confidence: 99%
“…Therefore, the c-BN films in previous reports are nonoriented polycrystalline. [10][11][12][13][14][15][16][17][18][19][20] We recently achieved the heteroepitaxial growth of phasepure c-BN(001) and (111) films on diamond (001) and (111) substrates by the ion-beam-assisted molecular beam epitaxy (MBE) method. 21) Furthermore, we revealed that a V=III ratio higher than 1 and a growth temperature (T g ) above 750 °C are necessary for the epitaxial growth of c-BN films on diamond substrates.…”
mentioning
confidence: 99%
“…The peaks of O1s at binding energies of 530.1, 531.5, and 533.2 ± 1 eV were assigned to FeOSi, FeBO, and BOC bonds, respectively . Furthermore, the peak of O1s at 532.9 eV for substrates tested with 3 and 5% boric acid‐base oil corresponded to B 2 O 3 in 3.54 and 3.12% atomic quantity, respectively . The Fe2p3 peak presents iron oxides on the wear scar surface of the substrates tested with boric acid+base oil .…”
Section: Resultsmentioning
confidence: 93%
“…41,42 Furthermore, the peak of O1s at 532.9 eV for substrates tested with 3 and 5% boric acid-base oil corresponded to B 2 O 3 in 3.54 and 3.12% atomic quantity, respectively. 43,44 The Fe2p3 peak presents iron oxides on the wear scar surface of the substrates tested with boric acid+base oil. 45,46 Fe, S, P, Zn, and O elements were detected in the XPS analyses of wear scar surfaces of the substrates, which were lubricated by 1, 3, and 5% ZDDP+base oil due to the decomposition of ZDDP under heat and load (see Table 4 and Figure 11).…”
Section: Tribochemical Analysis Of the Surfacesmentioning
confidence: 99%